Multivariate analysis of resistance components to Asian rust in soybean genotypes - Koga, Lucimara Junko; Canteri, Marcelo Giovanetti; Calvo, Éberson Sanches; Unfried, Jair Rogério; Garcia, Alexandre; Harada, Arlindo; Kiihl, Romeu Afonso de Souza (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this study was to detail the infection cycles of Phakopsora pachyrhizi Syd. & P. Syd. in soybean genotypes, in order to establish a group of the most promising genotypes for use as sourcesof resistance to Asian soybean rust. The infection cycle components were quantifi ed in 48 genotypes. The assessments consisted of: type of lesion, intensity of sporulation, severity, number of lesions and uredinias, and productivity of urediniospores. The cluster analysis formed four groups: A – developed the highest amount of disease; B – developed the lowest amount of disease; C – low initial resistance; and D – high initial resistance. All the genotypes of groups B, C and D had RB (redish-brown) lesions and varied for initial resistance, delayedresistance, intensity of sporulation, stability of the qualitative response, productivity of urediniospores, and number of days to reach 50% of the maximum severity. Qualitative responses and disease severity evaluations refl ect the combined effects of resistance on all the infection components and show practical importance in genotypes differentiation, regarding disease resistance. The genotypes of groups B, C and D presented qualitative and quantitative resistance, in different degrees, and they are promising genotypes as sources of resistance to Asian soybean rust.
Keywords: Glycine max; Phakopsora pachyrhizi; epidemiology; number of lesions; number of uredinias; horizontal and vertical resistance; quantitative and qualitative resistance.